Effects of melatonin on testicular tissue nitric oxide level and antioxidant enzyme activities in experimentally induced left varicocele - Semercioz, A; Onur, R; Ogras, S; Orhan, I (Maghira & Maas Publications, 2003)
OBJECTIVES: The pathophysiology of the testicular damage in varicocele have not been completely understood. There are several studies concerning the effects of increased seminal reactive oxygen species (ROS) and the role of nitric oxide (NO) in infertile patients with varicocele and antioxidants have been used successfully to decrease oxidative stress in testis. In this study, we determined the effects of melatonin on testicular NO and antioxidant enzyme levels and investigated whether melatonin can prevent or diminish testicular damage in adult rats with experimentally induced unilateral varicocele. METHODS: Thirty adult male Wistar rats were randomly divided into three groups. In group I, using midline incision left renal vein was exposed but not tied. In group II, left renal vein was partially ligated to create varicocele. In group III, after creation of varicocele, daily and fresh-prepared melatonin was administered intraperitoneally for 4 weeks. Histopathological examination was performed and tissue malondialdehyde (MDA), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and tissue NO levels were determined. RESULTS: In group II, there were severe degenerative changes of the germinal epithelium and atrophy of the seminiferous tubules in left testis. In group III, in which rats received melatonin intraperitoneally, there were focal areas showing decrease in spermatogenesis and some degenerative changes. Similarly, the levels of ROS and NO were significantly increased in testicular tissue of rats in group II, whereas group III rat testes in which melatonin was administered, showed increased antioxidant enzyme activity and decreased NO levels. CONCLUSION: Infertility related to varicocele has multiple pathophysiological mechanisms and the effect of ROS, NO and antioxidant defense system are contributing factors in the disease state. Melatonin, a potent free radical scavenger, administration might be helpful in the prevention or at least, in the delay of the severe effects of varicocele on testicular tissue.
Keywords: varicocele; testis; nitric oxide; reactive oxygen species; melatonin